Consumers’ Perception of Distribution Channel for the Malaysian Microtakaful Scheme: An Exploratory Study - Wahidah Shari; Asmadi Mohamed Naim; Mohamad Yazid Isa; Mohd Fikri Sofi; Nurul Aini Muhamed; Selamah Maamor; Shahrul Nizam Ahmad (Emerald Publishing Limited, 2025)
Indexed by Scopus/ERA